The effect of agricultural information provision on smallholders’ technology adoption and yield: experimental evidence from Ethiopia - Waje, Samuel Semma; Shano, Berhanu Kuma; Walelign, Solomon Zena; Kassie, Workineh Asmare (Frontiers in Sustainable Food Systems, 2024)
Introduction Lack of sufficient agricultural information has led smallholders’ to rely on traditional agricultural farming technologies in Sub-Saharan African countries, resulting in low adoption of modern inputs and low yield. Understanding the effect of information dissemination is essential for smallholder farmers in rural areas. Therefore, this study aimed to examine the effect of a randomized agricultural information provision on technology adoption and yield of cassava producers in Sodo Zuria, Offa, and Kindo Koysha Woredas in Wolaita Zone, South Ethiopia Regional Sate. Methods The study utilized panel data collected in two rounds from 1040 farmers in 2021 and 2023. A Randomized control trial (RCT) design was applied to evaluate the effect agricultural information provision on technology adoption and yields, comparing the results between treatment and control groups. The study employed three related information interventions for beneficiaries of the Ethiopian Rural Productive Safety Net Program: (i) agronomic technical information, (ii) productivity and profitability information, and (iii) pooled information on both treatments. Results and discussion The study found that agricultural information provision increases the adoption of modern agricultural technologies, land allocated to cassava, and yield. The provision of agricultural information is negatively related to access to media exposure, access to cell phones, and access to infrastructure while positively associated with participation in social groups, farm size, and farm income. Further policy research and evaluation are needed to assess the effectiveness of information intervention in different contexts and settings and factors that influence the improved cassava adoption and yield.